Modelling FLOCponics systems: Towards improved water and nitrogen use efficiency in biofloc-based fish culture. (May 2023) - Pinho, Sara M.; de Lima, Jéssica P.; Tarigan, Nurhayati Br; David, Luiz H.; Portella, Maria Célia; Keesman, Karel J.
Abstract : FLOCponics is an integrated agri-aquaculture system, in which water and nutrients from a biofloc-based fish culture are reused to fertilise soilless plants. This paper is the first modelling study that focuses on decoupled FLOCponics with the aim of investigating and discussing whether the integration of biofloc-based culture with soilless plant production increases the efficiency of food production in terms of resource use and by how much. For this purpose, a biofloc-based monoculture system with a total volume of the fish tanks of 15.2 m 3, and a FLOCponics system with similar biofloc system and a planting area of 33.6 m 2 was modelled. The simulation models of these reference systems were run for a period of five years, and water, nitrogen and total suspended solid balances in both systems were compared. In addition to this, various planting areas of the FLOCponics system were changed step-wise until the most suitable size was found. The results indicate that FLOCponics is 10% and 27% more efficient in using water and nitrogen, respectively, than the stand-alone biofloc system. Also, the integrated system results in a reduction of 10% in the amount of solids discharged. Optimisation of the planting area with respect to key model outputs led to an improved FLOCponics system, where the planting area of the system is expanded by a factor of 3.2. The findings presented in this study support the hypothesis that integrating a biofloc system with hydroponics makes biofloc-based fish culture more efficient in terms of resource use and wastes avoidance. Highlights: The resource use efficiency of a biofloc and a FLOCponics system is compared. The FLOCponics system is more efficient in using water than the biofloc system. Nitrogen use efficiency is higher in the FLOCponics than in the biofloc system. The FLOCponics system discharges 10% less solid waste than the biofloc system. FLOCponics can possibly be made more efficient by expanding the planting area.